SOCIO-ECONOMIC CONDITIONS OF PHARMACEUTICAL INDUSTRY PROFESIONAL TRAINING IN UKRAINE IN (50-60'S, 20TH CENTURY) - Slipchuk, Valentina L. (Educological discourse, 2016)
The article examines the socio-economic conditions of pharmaceutical industry professional training in Ukraine in the 50-60's, 20th century: the basic requirements to universities and colleges for work on physical education and sport in the UkrSSR; the article shows that during the future pharmaceutical industry specialists practices the Ukrainian higher and secondary medical (pharmaceutical) educational institutions were guided by the historic Twentieth Communist Party of the Soviet Union Congress decisions and instructions of the Ministry of Higher Education and Ministry of Health of the USSR and UkrSSR on training of skilled workers of the Soviet health care; methods to improve professional training of the pharmaceutical industry according to the economic development of society.